Rhodium(III)-catalyzed heteroatom-directed C–H allylation with allylic phosphonates and allylic carbonates at room temperature. Issue 4 (28th January 2016) - Jo, Hyeim; Han, Sangil; Park, Jihye; Choi, Miji; Han, Sang Hoon; Jeong, Taejoo; Lee, Seok-Yong; Kwak, Jong Hwan; Jung, Young Hoon; Kim, In Su
Abstract: The rhodium(III)-catalyzed mild and site-selective C–H allylation of 2-arylbenzo[ d ]thiazoles and 2-arylbenzo[ d ]oxazoles with allylic phosphonates and allylic carbonates is described. This transformation provides an efficient construction of C2-allylated, crotylated and prenylated 2-arylbenzo[ d ]thiazoles and 2-arylbenzo[ d ]oxazoles. In addition, this protocol can be applied to the formation of 2-arylbenzo[ d ]thiazole scaffolds containing an allylic alcohol group by using of 4-vinyl-1, 3-dioxolan-2-one and vinyl oxirane as coupling partners. Graphical abstract: